2018
DOI: 10.1016/j.bbr.2017.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive and enhancing effects of nicotine on food-seeking behavior

Abstract: The present study examined how systemic low doses of nicotine affect the microstructure of reinforced food-seeking behavior in rats. Rats were first given an acute saline or nicotine treatment (0.1-0.6mg/kg, with an inter-injection interval of at least 48h), and then a chronic saline or nicotine treatment (0.3mg/kg/day for 10 consecutive days). Immediately after each injection, rats were required to press a lever five times to obtain food that was available at unpredictable times (on average every 80s) with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…However, it is unclear as to how much nonattentional effects (response latencies) contribute to improvements in accuracy in this task. We also found an increase in collection latency at the highest dose, which may reflect effects on the motivation for reward and food-rewarded behaviors (Romero et al, 2018 ). This is difficult to compare to some key studies (Mirza & Stolerman, 1998 ; Stolerman et al, 2000 ) because of a lack of reporting on this parameter.…”
Section: Discussionsupporting
confidence: 56%
“…However, it is unclear as to how much nonattentional effects (response latencies) contribute to improvements in accuracy in this task. We also found an increase in collection latency at the highest dose, which may reflect effects on the motivation for reward and food-rewarded behaviors (Romero et al, 2018 ). This is difficult to compare to some key studies (Mirza & Stolerman, 1998 ; Stolerman et al, 2000 ) because of a lack of reporting on this parameter.…”
Section: Discussionsupporting
confidence: 56%
“…However, it is unclear as to how much non-attentional effects (response latencies) contribute to improvements in accuracy in this task. We also found an increase in collection latency at the highest dose which may reflect effects on the motivation for reward and food-rewarded behaviors [55]. This is difficult to compare to some key studies [31,54] due to a lack of reporting on this parameter.…”
Section: Discussionmentioning
confidence: 53%
“…These results are particularly striking considering that a similar microstructural analysis conducted by Cooper and van der Hoek of feeding behavior after administration of cocaine, another psychostimulant and anorectic substance, was associated with a complete suppression of feeding, with the duration of suppression proportional to the dose (Cooper & van der Hoek 1993 ). Additionally, a recent study by Romero et al employed microstructural analysis techniques to analyze the reinforcer-enhancing effects of nicotine on food-seeking behavior (Romero et al 2018 ). They found that lower doses of nicotine administered via injection increased the rate of food-seeking bouts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, microstructural meal pattern analysis shows that the acute administration of cocaine, a potent anorectic drug, decreases food intake in rats (Cooper & van der Hoek 1993 ). To date, only one study by Romero et al has used microstructural analysis to analyze components of feeding behavior in relation to nicotine intake; their study focused on the reinforcing effects on nicotine on food-seeking behavior (Romero et al 2018 ). However, there are currently no studies comparing the effects of nicotine on acute vs. long-term feeding behavior.…”
Section: Introductionmentioning
confidence: 99%